Margins of authority: Coke's Institutes and the epistemology of the string cite. Issue 1 (2nd January 2017) - Stern, Simon
ABSTRACT: Precedential authority has an important place in doctrinal explication and analysis in Anglo-American law. Efforts to manage these precedents visually, in sixteenth- and seventeenth-century England, display a variety of solutions to the question of where precedents belong and how to represent them. Sir Edward Coke's approach, in his Institutes (1628–44), was to place the citations in the margin; this way of managing textual authority connected legal concepts in a way that lent new significance to the citations. The discussion examines this development by considering it in relation to the introduction of perspective in visual art, in the early fifteenth century, and the use of infinitesimals in the new mathematics of the early seventeenth century.